Primary epithelioid sarcoma of the dura: Case report - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2002)
OBJECTIVE AND IMPORTANCE: Epithelioid sarcomas are rare mesenchymal neoplasms that occur most often in the extremities of young adults. Despite isolated reports of epithelioid sarcomas arising in the head and neck region, these lesions have not been described previously, to our knowledge, in the central nervous system. CLINICAL PRESENTATION: We present the case of an 18-year-old woman with a unique dural sarcoma that arose in the right frontotemporal region. As visualized on magnetic resonance imaging studies, the 4.5-cm tumor focally traversed the cranium to penetrate the galea, the temporal muscle, and subcutaneous tissue. No brain invasion was noted. INTERVENTION: Despite gross total removal and postoperative radiotherapy (59 Gy), a large recurrence was noted 5 months after surgery. Histologically, the partly necrotic tumor consisted of epithelioid and spindle cells showing widespread vimentin and variable cytokeratin as well as epithelial membrane antigen immunoreactivity. Ultrastructurally, the cohesive cells featured various organelles, intermediate filaments, junctions, and filopodia-containing intercellular spaces. CONCLUSION: With the inclusion of epithelioid sarcoma, the spectrum of central nervous system sarcomas continues to expand.
Keywords: dura; epithelioid sarcoma; immunohistochemistry; ultrastructure; SOFT-TISSUE SARCOMAS; DIFFERENTIATION; ANGIOSARCOMA; DIAGNOSIS; FEATURES; TUMOR; CD34